Clinical Relevance of Specific Cognitive Complaints in Determining Mild Cognitive Impairment from Cognitively Normal States in a Study of Healthy Elderly Controls - Ávila-Villanueva, Marina; Rebollo-Vázquez, Ana; Ruiz-Sánchez de León, José M.; Valentí, Meritxell; Medina, Miguel; Fernández-Blázquez, Miguel A. (Frontiers in Aging Neuroscience, 2016)
Introduction: Subjective memory complaints in the elderly have been suggested as an early sign of dementia. This study aims at investigating whether specific cognitive complaints are more useful than others to discriminate Mild Cognitive Impairment (MCI) by examining the dimensional structure of the Everyday Memory Questionnaire (EMQ). Material and Methods: A sample of community-dwelling elderly individuals was recruited (766 controls and 78 MCI). The Everyday Memory Questionnaire (EMQ) was administered to measure self-perception of cognitive complaints. All participants also underwent a comprehensive clinical and neuropsychological battery. Combined exploratory factor analysis and item response theory were performed to identify the underlying structure of the EMQ. Furthermore, logistic regression analyses were conducted to study whether single cognitive complaints were able to predict MCI. Results: A suitable five-factor solution was found. Each factor focused on a different cognitive domain. Interestingly, just three of them, namely forgetfulness of immediate information, executive functions and prospective memory proved to be effective in distinguishing between cognitively healthy individuals and MCI. Based on these results we propose a shortened EMQ version comprising 10 items (EMQ-10). Discussion: Not all cognitive complaints have the same clinical relevance. Only subjective complaints on specific cognitive domains are able to discriminate MCI. We encourage clinicians to the EMQ-10 as a useful tool to quantify and monitor the progression of individuals who report cognitive complaints.